PROFILING CHILDREN'S EARLY NUMERACY DEVELOPMENT THROUGH SINGING AS AN INTEGRATED PEDAGOGICAL APPROACH - Nuraini, Erlina; Maulana Trianggono, Mochammad; Zahro, Ianatuz (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early numeracy is fundamental to children's subsequent mathematical development; however, previous studies have predominantly emphasized instructional effectiveness through experimental designs while providing limited insight into how numeracy develops within authentic classroom practices. This study aimed to explore the profile of early numeracy skills among children aged 3–5 years, examine the implementation of the singing method, and analyze the factors influencing numeracy development at KB Miftahul Falah Pujer, Bondowoso. The study advances the conceptual understanding of singing by positioning it as an integrated pedagogical context rather than merely an instructional medium, revealing the progressive development of five interconnected numeracy competencies. This study employed a qualitative descriptive case study. The participants consisted of one principal, one classroom teacher, and children in Group A who were purposively selected because of their direct involvement in singing-based numeracy learning. Data were collected through non-participant classroom observations, semi-structured interviews, and document analysis, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The trustworthiness of the findings was ensured through source and method triangulation, member checking, and prolonged engagement. The findings indicate that children's numeracy developed progressively from procedural counting to conceptual understanding through the integration of rhythm, movement, manipulatives, and dialogic interaction. Flexible pedagogical implementation and multimodal learning experiences strengthened conceptual numeracy, while developmental readiness, teacher competence, classroom participation, and parental support collectively shaped children's mathematical development. These findings highlight singing as a developmentally responsive pedagogical approach for promoting sustainable early numeracy learning.